Combining inducible protein overexpression with NMR-grade triple isotope labeling in the cyanobacterium Anabaena sp. PCC 7120 - Dominique Desplancq; Corinne Bernard; Annie-Paule Sibler; Bruno Kieffer; Laurent Miguet; Noëlle Potier; Alain Van Dorsselaer; Etienne Weiss (BioTechniques)
The difficulty and expense of preparing protein samples highly enriched in stable isotopes is a bottleneck for structural studies by nuclear magnetic resonance (NMR) spectroscopy. We have developed a new regulatable expression/labeling vector system in the cyanobacterium Anabaena sp. PCC 7120 using the endogenous promoter of the nitrate assimilation nir operon. Standard proteins were overexpressed upon induction with NaNO3, yielding up to 250 mg/L of culture. When the cyanobacteria were grown in the presence of inexpensive 15N-, 13C-labeled mineral salts and 2H2O, the expressed polypeptides were highly (>90%) enriched in stable isotopes. Furthermore, the tight repression of the nir promoter upon induction allowed the production of the toxic oncoprotein E6. In addition, under these conditions, the malE31 protein, while insoluble in Escherichia coli, was found to be soluble in Anabaena. Together, these properties render the described system especially suitable for the production and/or triple labeling of recombinant protein samples. It represents an interesting alternative to conventional protein expression systems used in structural genomics.